Recursos financeiros em saúde nos munícipios gaúchos : atenção, gestão e financiamento um tripé indissociável e seus dilemas - Machado, Rebel Zambrano (2019)
This thesis has as research object the Health Financial Resources in the Gaucho Municipalities: attention, management and financing, an inseparable tripod and its dilemmas. The Unified Health System (SUS) is presented through its technical (care model), policy (management model) and economic (financing model) dimensions, aims to demonstrate the importance of their inseparability. It was also analyzed the conduction of the municipal health systems of the municipalities that compose the Metropolitan Macroregion of Porto Alegre, considering the scenario of economic and financial crisis of the Brazilian federal units. It is shown the perspective of the financial management of these systems, comparing selected indicators to evaluate whether they present a correlation between their results and the spendings of part of the state co-financing, in Rio Grande do Sul, for Primary Health Care. A mixed method was adopted in the study, exploring the quantitative and qualitative approaches, using analysis of tables, graphs and descriptive statistics and, for the verification of correlations between variables, for the purpose of the correlation analysis the Pearson method was used. In the qualitative analysis, the main instrument was the final report of the public hearings of the Legislative Assembly of Rio Grande do Sul, organized by the Special Commission regarding the Financial Sustainability of SUS and with the participation of the federated entities using a content analysis for the construction of categories that emerged from the hearings' participants speech. In light of the mixed method and methodological path adopted, represented the articulating axis between the quantitative and the qualitative approach, between theory and practice and through this process the movement of epistemological, theoretical and axiological categories present in it. The gramscian categories employed and the political strategies served as contributions for reality knowledge, as well as instrumental for analysis and action. The data's collection time series was from 2012 to 2017. This period was defined considering the legislation changes for the SUS' organization, which became networks. Narratives made in regard to the Health Policy converge to the diagnosis of underfunding in health as the central difficulty of the system. In this context, this research supports a different narrative of what is considered as consensus, defending the indissociability between care model, management model and financing model for SUS' sustainability. It is considered that, when pointing underfunding as SUS' biggest problem, it ends up concealing a set of management difficulties that cannot be isolated. Far more than SUS underfunding, the hegemonic model and the difficulties in the financial execution (spending quality) represent, for the researcher, the real dilemmas for the system. Thus, by placing the greatest responsibilities on insufficient resources, the real difficulties are shifted and the management issues of the system remain hidden.